Pengukuran Literasi Sains Siswa Melalui Isu Lingkungan Berdasarkan Kerangka Kerja Sains PISA 2025 - Pramita Nabilla Putri; Fida Rachmadiarti; Tarzan Purnomo; Muhammad Satriawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to measure students' scientific literacy of science concepts, especially environmental pollution. This study assesses the scientific literacy of eighth-grade students’ using a quantitative descriptive method, with a sample selected through random sampling. Data were collected through a scientific literacy test focused on environmental issues and reinforced with interview and students’ respons. The science literacy test contains 10 double-choice questions that have been validated and tested for reliability. The research results revealed that students' scientific literacy in three competencies falls within the profience category, specifically: explain phenomena scientifically (72%), construct and evaluate designs for scientific inquiry (53%), and research, evaluate and use scientific information (69%). The average scientific literacy score was 67%, indicating that junior high school students' scientific literacy needs improvement in competency 2. The findings of Indonesian students' performance in this assessment highlight the need to improve learning strategies to strengthen students' ability to engage in critical scientific investigations.